Uji kandungan fenolik total dan aktivitas antioksidan ekstrak etanol biji kelor (Moringa Oleifera L.) dan daun sirih cina (Peperomia Pellucida L.) - Hafidz, Rosyadah; Abdul, Ahwan; Ariastuti, Reni Ariastuti (Borobudur Pharmacy Review, 2025)
Moringa seed (Moringa oleifera L.) and Chinese betel leaf (Peperomia pellucida L.) extracts obtained using ethanol contain phenolic compounds that function as natural antioxidant compounds. research aimed to quantify the overall phenolic content and assess the antioxidant activity of both extracts using Folin-Ciocalteu and DPPH techniques. The extraction process was performed using the maceration technique with 96% ethanol as the solvent, after which analysis It was performed to determine the overall concentration of phenolic compounds and IC50 a measurement that served as an index of antioxidant power. The findings showed that the extract from Chinese betel leaves had a higher a total phenolic content of 91.02 mg gallic acid equivalents (GAE) was recorded. compared to Moringa seeds which had 54.90 mg GAE/g±0.47. Antioxidant activity testing revealed that the IC50 value of Chinese betel leaf extract reached 3,349 ppm, while moringa seed extract showed an IC50 value of 4,701 ppm. For comparison, vitamin C had a lower IC50 of 1,988 ppm. With IC50 values below 50 ppm, both extracts are categorized as very strong antioxidants.